Flux Connections Between Gluconate Pathway, Glycolysis, and Pentose–Phosphate Pathway During Carbohydrate Metabolism in Bacillus megaterium QM B1551 - Wushensky, Julie A.; Youngster, Tracy; Mendonca, Caroll M.; Aristilde, Ludmilla (Frontiers in Microbiology, 2018)
Bacillus megaterium is a bacterium of great importance as a plant-beneficial bacterium in agricultural applications and in industrial bioproduction of proteins. Understanding intracellular processing of carbohydrates in this species is crucial to predicting natural carbon utilization as well as informing strategies in metabolic engineering. Here we applied stable isotope-assisted metabolomics profiling and metabolic flux analysis to elucidate, at high-resolution, the connections of the different catabolic routes for carbohydrate metabolism immediately following substrate uptake in B. megaterium QM B1551. We performed multiple 13C tracer experiments to obtain both kinetic and long-term 13C profiling of intracellular metabolites. In addition to the direct phosphorylation of glucose to glucose-6-phosphate (G6P) prior to oxidation to 6-phosphogluconate (6P-gluconate), the labeling data also captured glucose catabolism through the gluconate pathway involving glucose oxidation to gluconate followed by phosphorylation to 6P-gluconate. Our data further confirmed the absence of the Entner-Doudoroff pathway in B. megaterium and showed that subsequent catabolism of 6P-gluconate was instead through the oxidative pentose-phosphate (PP) pathway. Quantitative flux analysis of glucose-grown cells showed equal partition of consumed glucose from G6P to the Emden-Meyerhof-Parnas (EMP) pathway and from G6P to the PP pathway through 6P-gluconate. Growth on fructose alone or xylose alone was consistent with the ability of B. megaterium to use each substrate as a sole source of carbon. However, a detailed 13C mapping during simultaneous feeding of B. megaterium on glucose, fructose, and xylose indicated non-uniform intracellular investment of the different carbohydrate substrates. Flux of glucose-derived carbons dominated the gluconate pathway and the PP pathway whereas carbon flux from both glucose and fructose populated the EMP pathway; there was no assimilatory flux of xylose-derived carbons. Collectively, our findings provide new quantitative insights on the contribution of the different catabolic routes involved in initiating carbohydrate catabolism in B. megaterium.